Preferensi Chironomidae (Diptera) memilih jenis media air untuk tempat bertelur - Bambang Sulistiyarto (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This study aimed to examine the preference of Chironomidae (Diptera) to choice the types of water media for ovipositor sites. Water media types that used in this study were: (A) water of African catfish pond (B) water media with 12.5 g of dry waste of African catfish pond (C) water media with 12.5 g of dry chicken manure ( D) water media with 12.5 g of dry grass and (E) water media as a control. The parameters observed, covering the days there were eggs and larvae of Chironomidae on water media, population of larval Chironomidae, body length of Chironomidae larvae and water quality. The results of this study indicated that Chironomidae tend to preferred places to ovipositor in water containing high nutrient and media that have the complexity of the habitat structure. Chironomidae began to ovipositor in the media provided on day 5th. The highest population Chironomidae larvae were obtained in water media containing dry grass. Average body length of Chironomidae larvae at 8th day age was 5.943 ± 0.875 mm. The water quality in this research was still in the optimal range for survival of Chironomidae larvae. The water temperature, pH, dissolved oxygen and TDS during the study ranged from 28.83 to 29.37 OC, 6.73 to 7.71, 3.40 to 6.93 mg/L, and 24 to 158 mg/L respectively. Key words : Chironomidae, ovipositor sites, water media types.